Accelerating Climate Resilience through National Frameworks for Weather and Climate Information Services: Progress, Partnerships, and Pathways Forward in Six African Countries - Ghosh, Aniruddha; Ndiaye, Ousmane; Grossi, Amanda; Teshome, Asaminew; Muriuki, Edward; Murage, Paul; Ahmed, Jemal Seid (2025)
This working paper examines progress in establishing National Frameworks for Weather, Water, and Climate Information Services (NFWWCS) across six African countries—Ethiopia, Kenya, Senegal, Ghana, Mali, and Zambia—supported by the AICCRA initiative. These frameworks aim to institutionalize climate services, transforming data into actionable information that strengthens agricultural resilience. The report highlights diverse pathways: Ethiopia’s education-based institutionalization, Kenya’s political endorsement, Senegal’s legally anchored system, Ghana’s private-sector engagement, Mali’s digital innovation amid insecurity, and Zambia’s alignment with national development plans. Common success factors include strong national ownership, gender-responsive delivery channels, integration of climate information with tangible resources, and South–South learning exchanges. Persistent challenges centre on financing and last-mile delivery. Climate-Smart Agriculture Investment Plans (CSAIPs) are emerging as a key mechanism to link climate services with economic priorities. Collectively, these efforts demonstrate how coordinated national and regional architectures can accelerate climate resilience and sustainable development across Africa.